ANÁLISIS DE LA RENTABILIDAD ECONÓMICAFINANCIERA Y ESTUDIO DEL CAPITAL DE TRABAJO EN GALTOR SUPERMERCADO DE LA CIUDAD DE LOJA, EN EL PERIODO 2013 - Pinta Caraguay, Diana Patricia (2015)
In the world of finance, accounting is a discipline of vital importance that lets out clearly and consistently the functions performed by the administrative person in the company and to have greater control of the performance of the activities, implementation of necessary a process of Economic and Financial Analysis and study Profitability of working capital through financial indicators to measure the profitability and investment capacity in the company established its economic solvency and then formulate and present a report analyzing profitability financial, to make known to the Manager and Administrator on the situations encountered during the process of thesis work, so to make the right decisions and consequently a better development of the same states. The thesis has as main objective the development of a "ECONOMIC ANALYSIS OF FINANCIAL PERFORMANCE AND STUDY OF WORKING CAPITAL IN" GALTOR "SUPERMARKET Loja PERIOD 2013" to facilitate financial decision making by officials. To develop the general objective specific objectives are as follows: Perform a general diagnosis of the economic and financial situation "GALTOR" Supermarket Loja City in the period 2013 Evaluate the economic and financial profitability and interpret their results, allowing establish proposals for better decision-making, apply the EVA (Economic 6 Value Added) financial indicator to measure the real profitability of enterprises and supply management to information necessary for making business decisions. Analyzing working capital and its influence on the profitability of the company in order to determine the causes that would affect the financial health of the company. Then based on the practical application of theoretical profitability analysis, using different methods and techniques to determine the changes in the accounting period under study, the vertical analysis to the Balance Sheet and Income Statement was first applied and thus assess the financial situation of 2013 period, then proceeded to apply the economic-financial indicators of profitability; them to help us meet the financial and economic situation of the company. EVA analysis indicator can assess, verify and determine the variation of liquidity obtained by the company. Working capital allowed evidence liquidity, solvency and indebtedness with which the company has. Based on this perspective the theoretical and practical process is based on methods, techniques and procedures for collection, analysis and interpretation of information that facilitated the planning, development and implementation of all the theoretical and practical content and thus determine a number of relevant results that have a direct bearing on the decision. 7 At the end of this thesis record of the findings and recommendations is left, among the most relevant is the application of an analysis of economic and financial profitability and working capital study that allows providing real and timely information to the directors of the company and contribute to sound decision-deciciones, the recommendations are aimed at improving the commercial management allowing so promote the advancement and progress of the supermarket.